Outcome of orthograde retreatment after failed apicoectomy: Use of a mineral trioxide aggregate apical plug - Mente, Johannes; Leo, Meltem; Michel, Annemarie; Gehrig, Holger; Saure, Daniel; Pfefferle, Thorsten (Journal of endodontics, 2015)
This controlled, single-center historic cohort study project evaluates treatment outcomes of a nonsurgical treatment approach after failed apicoectomy. The treatment outcomes of nonsurgical retreatment after a failed apicoectomy were evaluated clinically and radiographically. The study cohort consisted of teeth that had received primary root canal treatment and subsequent apicoectomy elsewhere before the patients presented with post-treatment disease. Orthograde retreatment and obturation using an apical mineral trioxide aggregate plug was performed by postgraduate students and endodontic specialists in 25 cases between 2004 and 2012. Pre-, intra-, and postoperative information and the potential effect on the retreatment outcome were evaluated and statistically analyzed using the chi-square test. Twenty-two patients with 23 teeth attended the follow-up examinations (recall rate = 92%). The follow-up periods ranged from 12 to 102 months (median = 35 months). Twenty teeth (87%) were classified as “success,” and 3 teeth were considered (17%) “failure.” The chi-square test confirmed that the preoperative factor “number of roots” had a statistically significant effect on treatment outcome (odds ratio = 0.08; 95% confidence interval, 0-1.76; P = .03). The factor “tooth location” was of borderline significance (odds ratio = 0.1; 95% confidence interval, 0-2.14; P = .05). The results of the present study suggest that orthograde retreatment combined with orthograde placement of an apical mineral trioxide aggregate plug is a promising long-term treatment option for teeth with postsurgical pathosis. The success rates were higher for single-rooted teeth. The use of cone-beam computed tomographic imaging in cases of inconclusive periapical radiographs is recommended to minimize the risk of misinterpretation when assessing treatment outcome.
Gesehen am 18.08.2017